Minority as a majority: Does it make a difference? - Taylor, Terrance J. (1998)
The relationship between race and crime has long been a primary concern of criminal justice researchers. Numerous studies have examined this relationship through the use of official statistics, self-reports, and victimization surveys. The results of these studies present multiple and often conflicting results. Studies examining official statistics and victimization data have generally found a significant difference in delinquency between White and minority juveniles, with minority juveniles responsible for more delinquency than White youth in terms of both incidence and seriousness. Self-report studies, on the other hand, have often found no differences between minority and White youth, or smaller differences than those reported in official statistics and victimization data. One structural element which has received little attention by researchers is numerical minority or majority status in a community. The terms minority and majority are generally used to describe groups based on their relative power in a society, regardless of their numerical proportion in specific areas. Yet researchers have alluded to the potential importance of numerical minority-majority status in examinations of such diverse areas as homicide rates, police expenditures, and fear of crime. This thesis will add to the debate by examining the relationship between race and crime in terms of numerical minority-majority status and self-reported delinquency within two public school districts. Three research questions are addressed. First, do African American and White youth differ in terms of self-reported attitudes and behaviors? Secondly, if differences do exist, does the city in which students reside have an impact? Finally, what role does numerical minority-majority status play? Data used here are taken from the cross-sectional component of the National Evaluation of the Gang Resistance Education and Training (G.R.E.A.T.) program, a study conducted by researchers from the University of Nebraska at Omaha during the Spring of 1995. While the larger evaluation included eleven cities purposely selected to represent the geographic and demographic diversity of the United States, this paper will examine only two sites: Kansas City and Omaha which provide a unique opportunity to examine the effect of minority-majority status on delinquency. The cities are similar in geographic location, historical development, and demographic composition. The cities differ, however, in terms of the demographic characteristics of their public school districts; African-American students comprise a majority of Kansas City public school students while they constitute a minority in Omaha. Findings suggests that race, city, and minority/majority status each have an independent impact on self-reported delinquency, but the effect of city of residence is more important than both race and minority/majority status. Additionally, these variables were much less powerful than other variables associated with social disorganization and anomie theories: specifically, peer delinquency, school environment, and school commitment